AUDIT SISTEM INFORMASI MENGGUNAKAN KERANGKA KERJA COBIT 4.1 PADA SIIX ELECTRONICS INDONESIA - Muhammad, Jefano Riezki; Amrizal, Amrizal (Computer Science and Industrial Engineering, 2021)
PT SIIX Electronics Indonesia is a company engaged in manufacturing the assembly of electronic goods such as scanners, keyboards, cellphones, and so on. This company uses a payroll system called FPCollector in the payroll process. The problem that occurs at this company is the occurrence of errors in calculating employee salaries and calculating salaries that are not transparent because employees only know the total salary each month without knowing how much the deduction is due to tardiness and absence for a month. The research object is PT SIIX Electronics Indonesia. The purpose of this study is to evaluate assessments and make recommendations based on a maturity level analysis of the FPCollector information system at PT SIIX Electronics Indonesia according to the COΒIT 4.1 standard. The use of this standard is because it is a general control standard for controlling information systems and has parameters that are able to provide a risk assessment of a company using maturity models.